2012
DOI: 10.1299/jsdd.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the Flow Disturbance Observer and Base Plate Jerk Feedback in a Pneumatic Positioning Stage

Abstract: Pneumatic actuation systems are commonly used to drive the positioning stage due to several merits. However, one of the critical demerits of the pneumatic systems is the problem of the compressibility, which results in the flow disturbance. Another problem of the positioning stage can be addressed to the vibration which occurs due to the active condition of the base plate. This paper concerns the mentioned two issues in a pneumatic positioning stage. In order to suppress the flow disturbance and to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In our preceding studies (8,9) , we showed that the BPJFB with positive polarity in a pneumatically actuated stage is the same as the base plate acceleration feedback with positive polarity in XY stages driven by the linear motors (10,11) . The only difference of these feedback controllers is based on the difference in the dynamics of actuation systems, which will be discussed later.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In our preceding studies (8,9) , we showed that the BPJFB with positive polarity in a pneumatically actuated stage is the same as the base plate acceleration feedback with positive polarity in XY stages driven by the linear motors (10,11) . The only difference of these feedback controllers is based on the difference in the dynamics of actuation systems, which will be discussed later.…”
Section: Introductionmentioning
confidence: 84%
“…2. Where the mechanical system is modeled as a 2-DOF system due to the suspension of base plate on the coil-type spring isolators by neglecting the vertical motion (8)(9)(10)(11)(12) , for which the equations of motion are defined as follows:…”
Section: Proposed Control Block Diagram and Related Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…As a control method of pneumatic actuators, proportional-derivative-double derivative (PDD 2 ) control (Kagawa, et al, 2000) is known. In our previous work (Wali and Wakui, 2012), we utilized this control scheme for the positioning of the pneumatic stage. The advantage of the PDD 2 control is that, by adjusting parameters of a PDD 2 controller, the desired damping and stiffness of a control system can be easily obtained.…”
Section: Introductionmentioning
confidence: 99%